Evaluation of Chromosome Abnormalities in Couples With Recurrent Spontaneous Abortions - Erol, Deniz; Elyas, Halit; Yüce, Hüseyin; Akın, Haluk (Fırat University, 2003)
Aim: Most of the cases with fetal loss are not associated with chromosomal abnormalities. If there is no another causative factor, cytogenetic analysis may reveal a balanced structural chromosomal rearrangement in any partner. In 3-5% of couples with at least 2 spontaneous abortions, one partner carries a balanced chromosomal rearrangement. The aim of this study is to investigate the balanced structural chromosomal rearrangements and serve the genetic counselling to the family about following gestation. Material and method: In this study, 80 couples with at least two spontaneous abortions or one spontaneous abortion and one stillborn admitted to the Fırat Medical Center were analysed. Chromosomes were obtained from peripheral blood lymphocytes by standart techniques. Chromosomal abnormalities were confirmed by FISH (fluorescent in-situ hybridisation) technique. Results: Three chromosomal polymorphic variants including two inv(9), one Yqh+ and one 13/14 Robertsonian translocation chromosome abnormality were found in 80 couples with recurrent spontaneous abortions. Chromosomal abnormality incidence including polymorphic variants in this study was determined to be 5%. These incidences are compatible with the literature. Conclusion: The evaluation of the chromosomal abnormalities in couples with recurrent spontaneous abortions is very important. These findings are essential to perform appropriate genetic counseling for the future pregnancies of these couples.

Amaç: Fetal kayıplı olguların büyük çoğunluğu kromozomal anormalliklerle ilişkili değildir. Başka bir nedensel faktör yok ise, sitogenetik analizler herhangi bir eşte dengeli bir yapısal düzenlenme ortaya koyabilir. İki veya daha fazla spontan abortusa sahip çiftlerde ise eşlerden biri %3-5 oranında dengeli bir kromozomal yeniden düzenlenmeye sahiptir. Bu çalışmanın amacı, tekrarlayan spontan abortuslu çiftlerde kromozomal dengeli yapısal yeniden düzenlenmeleri araştırmak ve bu ailelere sonraki gebelikleri hakkında genetik danışmanlık vermektir. Gereç ve yöntem: Bu çalışmada tekrarlayan spontan abortus şikayeti ile Fırat Tıp Merkezine başvuran en az iki spontan abortuslu veya bir spontan abortus ve bir ölü doğumlu 80 çift incelendi. Kromozomlar periferik kan lenfositlerinden standart sitogenetik tekniklerle elde edildi. Kromozomal anormalliği olan olguların metafaz örnekleri, FISH (floresans in-situ hibridizasyon) tekniği kullanılarak teyit edildi. Bulgular: Tekrarlayan spontan abortuslu 80 çiftte iki inv(9), bir Yqh+ olmak üzere 3 kromozomal polimorfik varyant ve bir 13/14 Robertsonian translokasyon kromozom anormalliği bulundu. Bu çalışmadaki kromozomal anomali insidansı polimorfik varyantlarla birlikte %5 olarak belirlendi. Bu insidans literatür ile uyumludur. Sonuç: Tekrarlayan spontan abortuslu çiftlerde kromozom anormalliklerinin değerlendirilmesi oldukça önemlidir. Bu çiftlerin daha sonraki gebelikleri için sağlıklı bir genetik danışmanlık verilmesinde bu bulgular esastır.
Tekrarlayan Spontan Abortuslu Çiftlerde Kromozom Anomalilerinin Değerlendirilmesi